Effects of appendicectomy on the course of ulcerative colitis. Issue 6 (1st December 2002) - Cosnes, J; Carbonnel, F; Beaugerie, L; Blain, A; Reijasse, D; Gendre, J-P
Abstract : Background: Appendicectomy reduces the risk of having ulcerative colitis. However, its effect on the natural history of ulcerative colitis remains uncertain. Aim: To determine whether appendicectomy reduces the overall severity of ulcerative colitis. Patients and methods: Appendicectomy status and smoking habits were specified by direct interview in 638 patients seen consecutively between 1997 and 2000. Severity of ulcerative colitis was assessed by reviewing therapeutic needs from the onset of colitis. Additionally, the annual incidence of flare up was assessed prospectively between 1997 and 2000 in patients who had not been colectomised. Results: The 10 year risk of colectomy was 16 (7)% in previously appendicectomised patients (n=49) compared with 33 (2)% in non-appendicectomised patients (n=589, p=0.05). Cox regression showed that previous appendicectomy and current smoking were independent factors protecting against colectomy (adjusted hazard ratio and 95% confidence intervals: 0.40 (0.20–0.78) and 0.60 (0.40–0.95), respectively). The respective proportions of appendicectomised and non-appendicectomised patients who required oral steroids and immunosuppressive therapy were not significantly different (67% v 70% and 27% v 19%, respectively). Between 1997 and 2000, ulcerative colitis was active for 48% of the time in appendicectomised patients (47 of 98 patient years) and for 62% of the time in non-appendicectomised patients (631 of 1024 patient years; p<0.01). Conclusion: Previous appendicectomy is associated with a less severe course of ulcerative colitis. The beneficial effect of appendicectomy on the risk of colectomy is additive to that of current smoking.